Assessment of the seismic vulnerability of an unreinforced masonry structure based on discrete-macro dynamic analyses - Chácara, César (2019)
UnReinforced Masonry (URM) structures experience severe damage due to in-plane and out-of-plane mechanisms when subjected to seismic actions. The assessment of the seismic vulnerability of URM generally requires complex analytical procedures consisting of the application of sophisticated numerical models. However, these models may request a high computational effort or may present an over-simplified scheme, mainly when the out-of-plane mechanisms are neglected. In this sense, a 3-dimensional macro-element model is here used for a preliminary assessment of the seismic vulnerability of a URM prototype characterized by an out-of-plane collapse mechanism. In this paper, the seismic vulnerability of this type of constructions is investigated by means of fragility functions in accordance with specific damage states and a given seismic input. The structural safety assessment was conducted by means of time history analyses with a limited computational effort. In addition, the evaluation of the limit states is here performed by means of an alternative approach named as Capacity Dominium based on the application of nonlinear static analyses.